Complete Uniportal Thoracoscopic Anatomic Lung Resection With Systematic Mediastinal Lymphadenectomy for Non–Small Cell Lung Cancer: Personal Experience of 326 Cases. Issue 2 (April 2020) - Deng, Youjun; Wang, Jiaqing; Mu, Juwei; Wang, Zheng; Wang, Guangsuo
Abstract : Background: With its growing popularity and potential outcome, complete uniportal thoracoscopic (CUT) surgery has been used in the treatment of thoracic diseases. This study aimed to summarize a personal experience of CUT anatomic lung resection with systematic mediastinal lymphadenectomy (CUT-ALR-SML) for non–small cell lung cancer (NSCLC) and to evaluate the feasibility and safety of CUT-ALR-SML in our institute. Materials and Methods: A total of 326 patients with NSCLC were chosen to undergo CUT-ALR-SML in our institute from August 2013 to July 2018. Data such as clinicopathologic characteristics and perioperative outcomes were reviewed in this article. Results: For the 326 cases of ALR, the specific procedures and the corresponding number of cases were as follows: segmentectomy, 90; lobectomy, 218; sleeve lobectomy, 9; ipsilateral lobe combined with segment resected synchronously (i-L+S), 6; and pneumonectomy, 3. A total of 31 cases required conversion to open surgery, and 4 cases were converted to multiportal thoracoscopic surgery. All patients underwent SML. The average mediastinal lymph node stations and mediastinal lymph nodes dissected under CUT-ALR-SML were 3.3±1.4 and 9.6±8.4, respectively. Approximately 99.7% of the patients acquired free resection margins. A total of 42 (12.9%) patients suffered from postoperative complications, and 1 patient died of pneumonia during the perioperative period. Conclusions: Complete uniportal ALR, particularly for segmentectomy and lobectomy is safe and feasible with low complication rates and excellent free resection margin rates. SML during complete uniportal thoracoscopic surgery adequately assesses the N2 lymph node. However, further studies need to be conducted to evaluate the role of CUT-ALR-SML in the treatment of NSCLC.